New record of Neosaimiri (Cebidae, Platyrrhini) from the late Middle Miocene of Peruvian Amazonia. Issue 146 (September 2020) - Marivaux, Laurent; Aguirre-Diaz, Walter; Benites-Palomino, Aldo; Billet, Guillaume; Boivin, Myriam; Pujos, François; Salas-Gismondi, Rodolfo; Tejada-Lara, Julia V.; Varas-Malca, Rafael M.; Antoine, Pierre-Olivier
Abstract: The Honda Group of La Venta, Colombia, has yielded a wide array of crown platyrrhine primates, documenting the late Middle Miocene epoch (ca. 13.1–12.6 Ma, Laventan South American Land Mammal Age). Although exceptional, this record represents only a snapshot of the evolutionary history of New World monkeys because virtually none of the primate taxa recorded at La Venta had so far been found elsewhere. We describe here few dental remains of a cebine platyrrhine discovered from Laventan deposits in the San Martín Department of Peru (Peruvian Amazonia). The primate dental specimens from that new fossil-bearing locality (TAR-31) are strongly reminiscent morphologically of the teeth of Neosaimiri fieldsi from La Venta. However, given that several aspects of the dental variability from TAR-31 are unknown, we prefer to provide an assignment with open nomenclature (i.e., N. cf. fieldsi ), instead of formally referring these remains to N. fieldsi, pending the discovery of additional specimens. The occurrence of Neosaimiri in Peru, in coeval deposits of La Venta, thus represents a second and southernmost record of that low-latitude genus in the Neotropics, thereby demonstrating its wide distribution along the northwestern edge of the Pebas Mega-Wetland System, in tropical western South America.